Low-dimensional compounds containing bioactive ligands. Part XIV: High selective antiproliferative activity of tris(5-chloro-8-quinolinolato)gallium(III) complex against human cancer cell lines - Litecká, Miroslava; Hreusová, Monika; Kašpárková, Jana; Gyepes, Róbert; Smolková, Romana; Obuch, Jakub; David, Tomáš; Potočňák, Ivan (Bioorganic & medicinal chemistry letters, 2020)
Four gallium(III) complexes, [Ga(ClQ)3]⋅MeOH (1 - MeOH), [Ga(ClQ)3] (1), [Ga(BrQ)3] (2), [Ga(dIQ)3] (3) and [Ga(CQ)3] (4), were prepared (H-ClQ = 5-chloro-8-quinolinol, H-BrQ = 7-bromo-8-quinolinol, H-dIQ = 5,7-diiodo-8-quinolinol, H-CQ = 5-chloro-7-iodo-8-quinolinol) and characterised by elemental analysis, IR and NMR spectroscopy. Single crystal structure analysis of 1 - MeOH confirmed that the complex has a molecular structure with gallium(III) metal ion coordinated in mer-fashion by N- and O-donor atoms of three ClQ ligands. Stability of all complexes in DMSO was proved by 1H NMR spectroscopy. The in vitro antiproliferative activity of 1 was evaluated against the A2780, MBA-MB-231 and HCT116 cell lines. Complex 1 displays higher antiproliferative activity (IC50 values in the range 2.1-6 μm) compared to the ClQ ligand and cisplatin; and a significant selective antiproliferative potency (IC50 = 136 μm, for normal MRC5pd30 cell line). Radical scavenging experiments revealed that complex 1 exhibits the highest antioxidant activity of the prepared complexes as well as the ligands.
Keywords: Drug Screening Assays, Antitumor; Humans; Antiproliferative activity; komplexní sloučeniny; Gallium; 5,7-Diiodo-8-quinolinol; 5-Chloro-8-quinolinol; Antineoplastic Agents; 5-Chloro-7-iodo-8-quinolinol; Quinolines; lidé; Gallium(III) complexes; proliferace buněk; Coordination Complexes; scavengery volných radikálů; Free Radical Scavengers; 7-Bromo-8-quinolinol; Antiradical activity; Cell Proliferation; screeningové testy protinádorových léčiv; nádorové buněčné linie; protinádorové látky; Cell Line, Tumor; galium; chinoliny